THE EFFECT OF SOCIAL SUPPORT, EMOTIONAL INTELLEGENCE,AND MINDFULNESS ON PSYCHOLOGICAL WELL-BEINGAMONG EMPLOYEES - Refandani Refandani; Retno Kurniasih (INDONESIAN JOURNAL OF BUSINESS AND ECONOMICS, 2025)
This study analyzes the influence of social support, emotional intelligence, and mindfulness on the psychological well-being of employees at PT KAI (Persero) Daop 5 Purwokerto using a quantitative approach. From a population of 140 office employees, 104 respondents were selected through purposive sampling. Data were collected using a questionnaire and analyzed using multiple linear regression (IBM SPSS 25). The results indicate that social support and mindfulness have a positive effect on psychological well-being, while emotional intelligence does not show a significant effect. The theoretical framework used was the Conservation of Resources (COR) theory, which emphasizes that individuals strive to maintain and develop psychological resources to preserve well-being. These findings suggest the need for organizations to strengthen social support in the workplace and develop mindfulness enhancement programs as strategies to maintain and improve employee psychological well-being, while also contributing to the development of COR theory application in the workplace context.